Rare mimicry of bone tumors: systematic review of xanthogranulomatous osteomyelitis and its therapeutic implications - Moreira, Vinícius R. G.; Silva, Henrique L.; Maia, Eduardo H. S.; Pereira, Jonas T. (International Journal of Research in Orthopaedics, 2025)
Xanthogranulomatous osteomyelitis (XO) is a rare chronic inflammatory lesion of bone that closely mimics malignant neoplasms. Its etiology and pathogenesis remain poorly defined, and only a small number of cases have been reported since the first description in 1984. The objective of this systematic review was to analyze all documented cases of XO to clarify clinical characteristics, diagnostic challenges, treatment strategies, and outcomes. A comprehensive search of PubMed, Scopus, and Embase, supplemented by reference screening, identified 26 well-documented cases. Data regarding demographics, anatomical distribution, clinical features, imaging findings, microbiology, pathology, treatment, and prognosis were extracted and synthesized. Patients ranged in age from 10 to 65 years, with a median of 32 years and a slight male predominance. The femur was the most frequently affected bone, followed by the tibia, ulna, humerus, pelvis, and spine. Pain and swelling were the predominant presenting features, while fever and systemic symptoms were less common but often led to misdiagnoses such as tuberculosis or malignancy. Imaging consistently suggested aggressive neoplasia, but histopathology confirmed the diagnosis in all cases, showing foamy histiocytes admixed with lymphocytes, plasma cells, and multinucleated giant cells. Microbiological cultures were positive in 35% of cases, most often Staphylococcus aureus, followed by Pseudomonas aeruginosa, Aspergillus spp., and Mycobacterium marinum. Treatment was primarily intralesional curettage with or without grafting, with wide resections performed only when malignancy could not be excluded preoperatively. Outcomes were uniformly favorable, with recurrence reported in only two cases after incomplete curettage. In conclusion, XO is a benign but deceptive entity that mandates biopsy for accurate diagnosis. Curettage with pathogen-specific antimicrobial therapy when indicated achieves excellent results, and multidisciplinary collaboration is essential to avoid unnecessary radical resections.